Employees’ Perception about Social Accounting Practice by Commercial Banks of Bangladesh - Tamanna, Mehdina Kabir (Asian Business Review, 2018)
In banking industry social accounting has become an important phenomenon now a days. This practice by commercial banks creates a bridge between society/country and banks. The bank employees are highly motivated to do this for societal concern as well as corporate benefit. This study is conducted on 100 employees of some commercial banks of Dhaka, Bangladesh. Random sampling method was used to select the respondents. The study reveals bank employees’ perception about social accounting which is carried out by their own banks. Banks’ main focus is society/community while doing social accounting. Statistical tools like (mean, standard deviation, variance, frequency, correlation analysis) are used to find out the result by using SPSS software. The study reveals there is a positive relationship between social accounting with corporate competitiveness & social interaction. The commercial banks have to come forward to involve in practicing social accounting for economic development of Bangladesh.